Vaccination using mutated receptor binding domains of SARS-CoV-2: Evidence for partial immune escape but not serotype formation - Chang, Xinyue; Liu, Xuelan; Martina, Byron; Zeltins, Andris; Augusto, Gilles; Vogel, Monique; Mohsen, Mona O.; Speiser, Daniel E.; Bachmann, Martin F. (Frontiers in Immunology, 2023)
SARS-CoV-2 has developed a number of Variants of Concern (VOC) with increased infectivity and/or reduced recognition by neutralizing antibodies specific for the receptor binding domain (RBD) of the spike protein. Extended studies of other viruses have shown that strong and broad viral escape from neutralizing serum antibodies is typically associated with the formation of serotypes. To address the question of serotype formation for SARS-CoV-2 in detail, we generated recombinant RBDs of VOCs and displayed them on virus-like particles (VLPs) for vaccination and specific antibody responses. As expected, mice immunized with wild type (wt) RBD generated antibodies that recognized wt RBD well but displayed reduced binding to VOC RBDs, in particular those with the E484K mutation. Unexpectedly, however, antibodies induced by the VOC vaccines typically recognized best the wt RBDs, often more than the homologous VOC RBDs used for immunization. Hence, these data do not reveal different serotypes but represent a newly observed viral evolution, suggesting a unique situation where inherent differences of RBDs are responsible for induction of neutralizing antibodies. Therefore, besides antibody (fine) specificity, other qualities of antibodies (e.g. their affinity) determine neutralizing capability. Immune escape of SARS-CoV-2 VOCs only affects a fraction of an individual’s serum antibodies. Consequently, many neutralizing serum antibodies are cross-reactive and thus protective against multiple current and future VOCs. Besides considering variant sequences for next generation vaccines, broader protection will be achieved with vaccines that induce elevated titers of high-quality antibodies.